Does oral lichen planus aggravate the state of periodontal disease? A systematic review and meta-analysis - Nunes, Gabriel Pereira [UNESP]; Pirovani, Beatriz Ommati [UNESP]; Nunes, Larissa Pereira [UNESP]; Silva, Arles Naisa Amaral [UNESP]; Morábito, Maria Juliana Sismeiro Dias [UNESP]; Nunes-Júnior, Nilson Antônio [UNESP]; Delbem, Alberto Carlos Botazzo [UNESP]; Ferrisse, Túlio Morandin [UNESP] (Springer Nature, 2022)
Background: The objective of this systematic review and meta-analysis (SRM) was to assess the evidence between the association of oral lichen planus and periodontal disease, evaluating the periodontal clinical parameters and biomarkers levels. Methods: This systematic review and meta-analysis followed PRISMA and was registered in PROSPERO (CRD42020181513). Searches were accomplished in databases for articles published until June 2021. The meta-analysis was performed with the variables: plaque index (PI), gingival index (GI), probing depth (PD), and clinical attachment loss (CAL). The mean difference was applied with a 95% confidence interval. Results: Six articles were included. Qualitative analysis showed the levels of biomarkers (matrix metalloproteinases, interleukins, and periodontal microbiological profile) are increased in subjects with periodontal disease and oral lichen planus. In the meta-analysis, these subjects also presented increases in all periodontal clinical parameters evaluated: GI—gingivitis 0.22 [0.14, 0.31] p < 0.0001 and periodontitis 0.12 [0.06, 0.19] p = 0.0003; PI—gingivitis 0.22 [0.12, 0.31] p < 0.0001 and periodontitis 0.15 [0.08, 0.23] p < 0.0001; PD—gingivitis 0.27 [0.06; 0.48] p = 0.0107 and periodontitis 0.11 [0.01; 0.21] p = 0.0299; and CA—periodontitis 0.06 [0.01, 0.12] p = 0.0176. Conclusions: Evidence suggests a significant relationship between the severity of periodontal disease and the presence of oral lichen planus. Although the association is biologically plausible, further studies are needed using populations and well-defined biochemical and clinical outcomes with consideration of potential confounding factors. Clinical relevance: This SRM provides information on the interaction between OLP and periodontal disease and guides clinicians to make evidence-based decisions and suggests recommendations for further high-quality studies.
Keywords: Evidence-based dentistry; Meta-analysis; Oral lichen planus; Periodontal disease; Systematic review